(untitled) - Anderson, Laurie Halse (New York, 2016)
As the Revolutionary War rages on, Isabel and Curzon are reported as runaways, and the awful Bellingham is determined to track them down. With purpose and faith, Isabel and Curzon march on, fiercely determined to find Isabel's little sister Ruth, who is enslaved in a Southern state.
Keywords: Hoa Kỳ; Lịch sử; Cách mạng, 1775-1783